The Diminishing Power of One? Welfare State Retrenchment and Rising Poverty of Single-Adult Households in Sweden 1988–2011. (21st October 2019) - Alm, Susanne; Nelson, Kenneth; Nieuwenhuis, Rense
Abstract: In this study, we analyse the sharp rise in poverty among working-age singles and single parents in Sweden. In a dual-earner society like Sweden, we show that the return of mass unemployment in combination with the retreat of a generous and inclusive welfare state have substantially increased the poverty risks of single-adult households, who cannot rely on the income buffering effect of the family. Whereas cutbacks to unemployment benefits have been detrimental for the relative income position of single-adult households, the poverty risks of couples with and without children are much less affected. Individual-level characteristics of the poor persons themselves provide little explanatory leverage for why trends in poverty diverge by family form. Our results raise a number of issues of relevance for the wider academic debate about the capacity of the welfare state to adequately respond to both old and new social risk groups.